Transformasi Konflik Aceh dan Relasi SosialPolitik di Era Desentralisasi - Zainal, Suadi (UI Scholars Hub, 2016)
This article aims to analyze the settlement of a prolonged conflict between the Free Aceh Movement (Gerakan Aceh Merdeka/GAM) and the Indonesian Government through a Memorandum of Understanding (MoU) of Helsinki that had implications on changing the law for Aceh. Some previous studies stated that Memorandum of Understanding (MoU) as a win-win solution has been working well and give a better chance to end the separatist conflict in Aceh. However, This article shows that MoU Helsinki is only bring negative peace to Aceh, because its implementation through Law on Governing Aceh (LoGA) has reduced authorities of Aceh to govern itself and it does not transform the structure and relationship between Aceh and the Government of Indonesia to the balanced ones, although LoGA has provided opportunities for economic, social and political development in Aceh. The Peace agreement (MoU Helsinki) and LoGA were carried out and resulted in a compromise and consensus in the socio-political in Aceh. This article based on research using qualitative methods. The data collect from primary sources and secondary sources.